Effects of Fluid Treatment With Hydroxyethyl Starch on Renal Function in Patients With Aneurysmal Subarachnoid Hemorrhage. Issue 3 (July 2016) - Kunze, Ekkehard; Stetter, Christian; Willner, Nadine; Koehler, Stefan; Kilgenstein, Christian; Ernestus, Ralf-Ingo; Kranke, Peter; Muellenbach, Ralf M.; Westermaier, Thomas
Abstract : Background: Recent reports have doubted the efficacy and safety of hydroxyethyl starch (HES) for volume resuscitation. HES has been reported to promote renal insufficiency particularly in sepsis and trauma patients. This analysis investigated the effects of HES 6% 130/0.4 for fluid therapy in patients with intact renal function who suffered aneurysmal subarachnoid hemorrhage (SAH). Methods: This retrospective analysis included 107 patients and was conducted in the framework of a clinical trial assessing the efficacy of magnesium sulfate in SAH. Because magnesium is renally eliminated, patients with renal insufficiency had been excluded. Standard therapy after aneurysm occlusion included the daily administration of HES 6% 130/0.4. Serum and urine creatinine and fluid balance were measured daily. Results: Patients received a daily mean of 1101±524 mL HES and 3353±1396 mL Ringer's solution. The highest creatinine values were recorded on day 3 after admission (0.88±0.25 mg/100 mL) and continuously decreased thereafter. In 6 patients, creatinine values temporarily increased by >0.3 mg/100 mL but recovered to admission values at the end of the observation period. Conclusions: Concerning renal function, the first days after SAH seem to be a vulnerable phase in which a variety of interventions are performed, including contrast-enhanced neuroradiologic procedures. In this period, HES 6% 130/0.4 should be administered with caution. However, no patient suffered from renal failure and required temporary or permanent renal replacement therapy. These results suggest that the administration of HES 6% 130/0.4 is safe in SAH patients without preexisting renal insufficiency.